2019
DOI: 10.1371/journal.pmed.1002870
|View full text |Cite
|
Sign up to set email alerts
|

A novel nutritional supplement to reduce plasma homocysteine in nonpregnant women: A randomised controlled trial in The Gambia

Abstract: Background Infant DNA methylation profiles are associated with their mother’s periconceptional nutritional status. DNA methylation relies on nutritional inputs for one-carbon metabolic pathways, including the efficient recycling of homocysteine. This randomised controlled trial in nonpregnant women in rural Gambia tests the efficacy of a novel nutritional supplement designed to improve one-carbon-related nutrient status by reducing plasma homocysteine, and assesses its potential future use in prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Betaine or other one-carbon sources are recommended to be considered to combine with B vitamins supplementation to ameliorate homocystinuria [ 46 ]. However, only one RCT conducted in nonpregnant women in Gambia has evaluated the efficacy of supplementation with B vitamins plus betaine for 12 weeks on lowering homocysteine concentrations [ 20 ]. They have reported that the novel supplement (daily supplementation: 800 μg folic acid, 2.8 mg vitamin B 6 , 5.2 μg vitamin B 12 and 4 g betaine) reduces plasma homocysteine concentration by 2.32 μmol/L compared with the baseline and is more effective than a traditional supplement containing 15 micronutrients without betaine [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Betaine or other one-carbon sources are recommended to be considered to combine with B vitamins supplementation to ameliorate homocystinuria [ 46 ]. However, only one RCT conducted in nonpregnant women in Gambia has evaluated the efficacy of supplementation with B vitamins plus betaine for 12 weeks on lowering homocysteine concentrations [ 20 ]. They have reported that the novel supplement (daily supplementation: 800 μg folic acid, 2.8 mg vitamin B 6 , 5.2 μg vitamin B 12 and 4 g betaine) reduces plasma homocysteine concentration by 2.32 μmol/L compared with the baseline and is more effective than a traditional supplement containing 15 micronutrients without betaine [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, only one RCT conducted in nonpregnant women in Gambia has evaluated the efficacy of supplementation with B vitamins plus betaine for 12 weeks on lowering homocysteine concentrations [ 20 ]. They have reported that the novel supplement (daily supplementation: 800 μg folic acid, 2.8 mg vitamin B 6 , 5.2 μg vitamin B 12 and 4 g betaine) reduces plasma homocysteine concentration by 2.32 μmol/L compared with the baseline and is more effective than a traditional supplement containing 15 micronutrients without betaine [ 20 ]. Results of this study indicate that the combination of B vitamins and betaine may be a more effective nutritional supplement to reduce homocysteine concentration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If these immune-regulatory effects can be transmitted to the next generation, the intestinal immune function of chicken offspring may be enhanced. Numerous studies have proven that a changed phenotype of the parents induced by epigenetic factors—including dietary components—could be partly inherited by the offspring ( Li et al., 2018 ; James et al., 2019 ; Wu et al., 2019a ). It is worth mentioning that, in the colonic cells, a derivative of stevioside could affect DNA methylation, which is an important kind of epigenetic modification ( Mokarram et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%